A hybrid modeling and optimization approach for scheduling problems of assembly automation processes. (September 2016) - Pang, Yan; Xia, Hao
Dynamics of assembly automation systems involve the interaction of discrete-event and continuous-variable dynamics. Hence, a hybrid model is a natural framework for scheduling tasks in assembly automation processes. This study indicates that a weighted scheduling problem can be transformed into a weighted time-optimal problem for hybrid systems. In particular, it shows that the problem can be cast as a constrained optimization problem with inequalities quantifiers. In order to obtain quantifier-free inequalities, quantifier elimination techniques are used. Based on the quantifier-free inequalities, the scheduling problem of the assembly manufacturing process can be solved using linear programming methods. Applicability and simulation results are provided to illustrate the performance of the developed algorithms.